(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Our previous studies have demonstrated that raised IOP can contribute to an increase in the severity of inflammatory processes in the anterior segment. Given the involvement of free radical processes in the pathogenesis of uveitis, it is reasonable to use antioxidative agents for the treatment of the disease. The naturally occurring dipeptide carnosine (beta-alanyl-L-histidine) is a highly bioavailable low-molecular hydrophilic antioxidant with a direct effect on certain oxidant species and indirect effect on the system protecting the body from radicals; it contributes to membrane stabilization and can improve inflammatory processes. Purpose: To examine the features of the clinical course of experimental anterior uveitis developing in the presence of ophthalmic hypertension (OHT), and to improve the course with dipeptide carnosine. Material and Methods: Thirty-four rabbits were divided into three groups (group 1, 10 animals with induced allergic uveitis; group 2, 12 animals with OHT induced prior to experimental allergic uveitis; and group 3, 12 animals treated with carnosine for experimental allergic uveitis in the presence of OHT). Animals underwent biomicroscopy, ophthalmoscopy and tonometry. The number of white blood cells (WBC) in the aqueous humor of the anterior chamber was assessed microscopically, and total protein concentration was determined with the Lawry assay. Results: There were significant differences in the conjunctival and scleral injection (р=0.0001), pattern of keratic precipitates (р=0.0009), anterior chamber content (р=0.0034), pattern of posterior synechiae (р=0.0025), vitreous opacity (р=0.0338), and fundus pathology (р=0.0001) between groups of anterior uveitis-only and that with OHT. Even at four weeks of induced anterior uveitis, the number of WBC and the total protein in the aqueous humor of the anterior chamber were 14.3% (p > 0.05) and 27.5%, respectively, higher in in eyes of group 2 compared to eyes of group 1. The course of inflammatory process was significantly more severe in eyes with anterior uveitis in the presence of OHT than in eyes with uveitis-only, based on the comparison in major clinical signs in the anterior and posterior segments. Binocular instillation of carnosine solution in the conjunctival sac for 4 weeks resulted in a significant decrease in the severity of inflammatory process in the anterior and posterior segments in eyes of group 3, leading to an improved clinical picture and restoration of the blood-aqueous barrier and ciliary body transport, with a 45.8% decrease in the WBC and 31.6% decrease in total protein in the aqueous humor of the anterior chamber in treated eyes compared to untreated eyes with induced non-infectious anterior uveitis in the presence of OHT (р < 0.01). Заключение: Участие карносинов в терапии регимен для очернной inflamation в решении полученных IOP может неуклонно ликвидировать внешний вид и изменить ликвидацию скорости.